(untitled) (Third Sector Social Economic Review, 2022)
Migration is a phenomenon that has important effects on the political, economic and cultural structure of countries. The changes caused by this phenomenon on these structures are important in terms of enabling the reconstruction of societies. In this study, annual data for the period 2008-2021 were used. The relationship between internal migration and unemployment was examined for Level 1 Regions in Turkey. The stationarity test of the variables was done by Nazlıoğlu-Karul (2017) Panel Fourier unit root test. Both internal migration and unemployment variables have a unit root. The causality relationship between the variables was examined with the Dumitrescu-Hurlin (2012) test. According to the results obtained, a one-way causality relationship was found from internal migration to unemployment in Turkey. The empirical findings obtained in the study show that the internal migration movement, which is the effect of the push and pull factors of the Level 1 regions increases unemployment in Turkey. Another important finding is that the internal migration movement between the regions has an increasing effect on unemployment in the migrated regions, especially due to the fact that it is carried out to industrialized regions.